2018
DOI: 10.3847/1538-4357/aaa244
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Ages of Star Clusters in the Small Magellanic Cloud: Constraints on the Interaction History of the Magellanic Clouds

Abstract: We present a new study of the spatial distribution and ages of the star clusters in the Small Magellanic Cloud (SMC). To detect and estimate the ages of the star clusters we rely on the new fully automated method developed by Bitsakis et al. Our code detects 1319 star clusters in the central 18 deg 2 of the SMC we surveyed (1108 of which have never been reported before). The age distribution of those clusters suggests enhanced cluster formation around 240 Myr ago. It also implies significant differences in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 43 publications
0
35
0
7
Order By: Relevance
“…These populations follow the distribution of star formation in the SMC, which is predominantly along the bar of the SMC, and extend to the LMC through the MB. This is depicted from the star cluster (especially for those with ages <100 Myr) distribution of the SMC (Bitsakis et al 2018). A further detailed analysis of identified massive star populations will be presented in our following papers.…”
Section: Multiwavelength Time-series Datamentioning
confidence: 97%
“…These populations follow the distribution of star formation in the SMC, which is predominantly along the bar of the SMC, and extend to the LMC through the MB. This is depicted from the star cluster (especially for those with ages <100 Myr) distribution of the SMC (Bitsakis et al 2018). A further detailed analysis of identified massive star populations will be presented in our following papers.…”
Section: Multiwavelength Time-series Datamentioning
confidence: 97%
“…multiple peaks of star formation in the past few hundred million years (Yoshizawa & Noguchi 2003;Harris & Zaritsky 2009;Indu & Subramaniam 2011), may have a different effect on the two galaxies. For example, Bitsakis et al (2017Bitsakis et al ( , 2018 studied the distribution and ages of star clusters in the LMC and SMC and found that the star clusters at the central regions were younger in the SMC than in the LMC. Therefore, if SMC RSGs are younger, then perhaps this may indicate that they have lost less mass, assuming the MLR is the same, so less material is around them.…”
Section: Comparison Between the Lmc And Smcmentioning
confidence: 99%
“…The SMASH dataset provides the opportunity to re-derive a star cluster catalog for the MCs using uniform data and cluster detection techniques which should be more spatially complete than previous searches. This new effort aims to overcome shortcomings of recent algorithmic detection efforts (see Bitsakis et al 2017Bitsakis et al , 2018Piatti 2018a,b) by conducting a well-characterized crowdsourced visual search of the SMASH imaging. This technique continues the long tradition of visual cluster identification across the Local Group, and builds on the legacy of crowdsourced cluster identification in the Andromeda Galaxy (Johnson et al 2015), which demonstrated the capability and robustness of this methodology.…”
Section: Star Cluster Searchmentioning
confidence: 99%